Evaluasi Kesesuaian Lahan Untuk Tanaman Padi dan Palawija pada Lahan Sawah di Kecamatan Sawan Kabupaten Buleleng Berbasis Sistem Informasi Geografis - HALOHO, MESI BR; DIBIA, I NYOMAN; TRIGUNASIH, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Evaluation of Land Suitability for Paddy and Secondary Crops on Rice Fields in Sawan District, Buleleng Regency, Based on Geographical Information System This study aims to determine the actual and potential of land suitability, limiting factors, assumptions of improvement efforts, land use management, and making land suitability maps and land use direction maps for rice and secondary crops. The plants evaluated in this study included rice, soybeans, green beans, peanuts, and maize. This research was conducted in Sawan District, Buleleng Regency, from July 2020 to October 2020. Based on the intercropping of soil types map and the slope, seven homogeneous land units were obtained. The research method used was a land evaluation survey, analysis, and land suitability classification. It is based on the criteria for plant growth requirements, according to Ritung et al . (2011), which were matched to the quality/characteristics of the land. The results research show that the actual land suitability classes for rice and secondary crops are from S1 (very suitable) to S3 (suitable to marginal). The limiting factors in the research area include temperature, rainfall, dry months, humidity, drainage, texture, coarse materials, P2O5, K2O, and slopes. Improvement of land suitability classes can be carried out through several factors, except for temperature, humidity, coarse materials, surface rock, and rock outcrops because they are permanent limiting factors. Improvement efforts for limiting factors that can be improved are repairing the drainage system, fertilizing, adding organic matter, mulching, and making terraces. The potential land suitability classes for rice and secondary crops that are evacuated are from S1 (very suitable) to S3 (suitable marginal) with the limiting factors for temperature, rainfall, humidity, coarse material, surface rock, and rock outcrops. The recommendations for land use in SLH RCISw, RCKISw, LCKIISw, RCKIISw, and LCKIIISw are rice, soybeans, and green beans. RCKIIISw and RCKIVSw are soybeans, peanuts, and maize.